Industrial Corridors – The New Paradigm for Economic Development in India: Examining the Challenges of Implementing Industrial Corridors in India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This paper examines the emergence of new models of industry led economic development in India such as Special Investment Regions and Industrial Corridors. As the Indian policymakers push for this Model for economic transition challenges related to Governance planning, Land Acquisition and Funding emerge.